Two new species and additional records of "small"-eyed Quedius from the Eastern Mediterranean (Coleoptera: Staphylinidae: Staphylininae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2007)
Three Quedius species from the Eastern Mediterranean are (re-)described and illustrated: Quedius (Raphirus) endogeus sp. n. (Greece), Q. (Microsaurus) atricapillus Reitter, 1900 (Turkey), and Q. (M.) apfeli sp. n. (Cyprus). Additional records of some species of the subgenus Microsaurus Dejean, 1833 are reported, among them first records from Turkey, Lebanon, and Israel.KeywordsColeoptera, Staphylinidae, Staphylininae, Quediina, Quedius, Palaearctic region, Eastern Mediterranean, taxonomy, new species, new records, endogean fauna.Nomenclatural Actsapfeli Assing, 2007 (Quedius (Microsaurus)), spec. n.endogeus Assing, 2007 (Quedius (Raphirus)), spec. n.